Globally Important Agricultural Heritage Systems in Japan: investigating selected agricultural practices and values for farmers - Tapan Kumar Nath; Makoto Inoue; Yim Ee Wey; Saori Takahashi (International Journal of Agricultural Sustainability)
The concept of Globally Important Agricultural Heritage Systems (GIAHS) evolved as a global collaborative endeavour to identify and protect a mosaic of traditional agro-ecosystems and landscapes that are rich in biodiversity and have both cultural and livelihood importance for farmers. In this study, we document prominent features of selected agricultural practices and GIAHS values using empirical data from two GIAHS sites in Japan. The designation of GIAHS in traditional farming landscapes encouraged farmers to maintain age-old practices, protect local crop varieties, revitalize discontinued agriculture (e.g. swidden agriculture), and add nature-based technologies such as micro hydroelectric projects. Farmers’ cooperative efforts have been reinforced, community bonding has been strengthened, local festivity has been expanded, and relationships with numerous government and non-government organizations have been formed. Their farm productivity remained modest, but household income increased owing to branding, certification, internet marketing, and farm stays supported by partnerships. The above attributes of GIAHS are closely linked to the principles of sustainable and regenerative agriculture. The primary issues for the viability of GIAHS are aging farmers and the depopulation of younger people. Lessons from this study could be valuable for developing GIAHS in countries where local agricultural practices and farmer livelihoods are under threat.